Harold Foote Gosnell papers - Gosnell, Harold F. (Harold Foote), 1896-1997.
Chiefly subject files consisting of correspondence, memoranda, reports, research data, maps, charts, printed and near-print material, and miscellany relating principally to projects Gosnell conducted for various government agencies. Documents a study (1937-1939) on state and regional planning for the U.S. National Resources Committee; studies (1943-1949) on government information services, especially those of the U.S. Office of War Information and the U.S. Dept. of State; and analyses of foreign elections for the U.S. Central Intelligence Agency, especially in the Philippines (1953, 1955), Indonesia (1955), and the Sudan (1958). Correspondents include Joseph Barnes, Milton Stover Eisenhower, and Charles W. Eliot.
Library of Congress Prints and Photographs Division.
Political scientist, educator, and government consultant.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Barnes, Joseph, -- 1907-1970 -- Correspondence; Eisenhower, Milton Stover, -- 1899-1985 -- Correspondence; Eliot, Charles W. -- 1899-1993 -- Correspondence; United States. -- Central Intelligence Agency; United States. -- Department of State; United States. -- National Resources Committee; United States. -- Office of War Information; Elections -- Indonesia; Elections -- Philippines; Elections -- Sudan; Information services; Regional planning; Consultants; Educators; Political scientists